2015
DOI: 10.1016/j.ijscr.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Meckel’s diverticulum mesentery along with its band forming a hernial sac: A rare case of internal herniation

Abstract: HighlightsMeckel’s diverticulum (MD), a remanant of omphalomesenteric duct, is the most common congenital malformation of GIT.Most patients are asymptomatic. Patients develops symptoms due to its complications like bowel obstruction, hemorrhage, diverticulitis, Littre’s hernia or perforation.Case presented with persistent features of subacute intestinal obstruction due to herniation of bowel loops through unusual mesentery of Meckel’s diverticulum extending from base of diverticulum to the band which was runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…4,5 In one literature review, only 6%-12% of cases were diagnosed preoperatively. 6 Rarely, direct compression of the small bowel by the mesodiverticular band, rather than an internal hernia, as in our case, may be the cause of small bowel obstruction due to mesodiverticular band, as has been described in a newborn. 2 Other rare complications associated with a mesodiverticular band have included axial torsion of the diverticulum itself due to the band 7 and aneurysmal rupture of a mesodiverticular band artery, with significant peritoneal hemorrhage, 8 both in adults.…”
Section: Discussionsupporting
confidence: 66%
“…4,5 In one literature review, only 6%-12% of cases were diagnosed preoperatively. 6 Rarely, direct compression of the small bowel by the mesodiverticular band, rather than an internal hernia, as in our case, may be the cause of small bowel obstruction due to mesodiverticular band, as has been described in a newborn. 2 Other rare complications associated with a mesodiverticular band have included axial torsion of the diverticulum itself due to the band 7 and aneurysmal rupture of a mesodiverticular band artery, with significant peritoneal hemorrhage, 8 both in adults.…”
Section: Discussionsupporting
confidence: 66%
“…It could be difficult to diagnose Littre’s hernia before operation [3] . Most of them are clinically silent and often incidentally found during laparotomy or in inguinal incision as in our case [4] .…”
Section: Discussionmentioning
confidence: 68%
“…Internal herniation by the Meckel’s diverticulum causing SBO is rare, and several cases of internal herniation due to adhesion of inflamed end of the Meckel’s diverticulum to the corresponding base of mesentery have been reported by Papaziogas et al [ 10 ] and Lin et al [ 11 ]. Additionally, Pandove et al reported a case of an adhesion band extending from the tip of the diverticulum to the adjacent mesentery, in addition to internal herniation of bowel into a sac formed by unusual mesentery of the Meckel’s diverticulum and the adhesion band [ 12 ]. In a case reported by Zhang et al, the tip of the diverticulum was densely adhered to the adjoining mesentery, forming a narrow ring through which small intestine had drilled through, resulting in gangrene of the herniated small bowel [ 13 ].…”
Section: Discussionmentioning
confidence: 99%